Dietary Intake and Frequency of Physician Consultations, Infections, and Antibiotic Treatments in the Quebec Longitudinal Study of Child Development - Pullen, Celine C (University of Ottawa (Canada), 2010)
Many Canadian children are not eating in accordance with the recommendations of Canada's Food Guide. The health effects of such behaviours are widely unknown. Using the Generalized Estimating Equations technique and data from the Quebec Longitudinal Study of Child Development, this study longitudinally explored the effects of low, medium, and high dietary intake of grain products, vegetables, fruits, milk and alternatives, and meat and alternatives on three indicators of child health, namely: the frequency of physician consultations, infections, and antibiotic treatments, in children from age1 to 7. Using multivariable models, high intake of vegetables (two or more times per day) was found to significantly reduce the risk of physician consultations and antibiotic treatments. Low intake of meat and alternatives (less than once per day) reduced the risk of physician consultations, and high intake of fruits (two or more times per day) reduced the risk of general infections.
Keywords: Health Sciences, Epidemiology.